Analysis of the predicting factors of recurrent wheezing in infants - Jia Zhai; Yingxue Zou; Jie Liu; Xingnan Jin; Cuian Ma; Jiao Li; Run Guo; Bing Huang (BMC, 2019)
Abstract Background Clinically, asthma in children under 5 years old is under estimated because lack of diagnostic criteria. The current study was, therefore, designed to identify the predicting factors for recurrent wheezing in infants. Methods One hundred forty-five infants under 3-year old hospitalized with respiratory diseases were enrolled into this study. Patients were followed up for one-year period after being discharged from the hospital and were, then, divided into recurrent wheezing group and non-recurrent wheezing group based on whether there was recurrent wheezing or not. Wheezing or recurrent wheezing was specifically monitored in addition to blood tests for allergic and respiratory diseases. Results The prevalence of eczema and respiratory syncytial virus (RSV) infection were significantly higher in recurrent wheezing group than in control group (74.2% vs 45.8%; 32.3% vs. 13.3%, respectively, both P < 0.05); the percentage of blood eosinophil and serum eosinophil-derived neurotoxin (EDN) concentration at admission were also higher in recurrent wheezing group than in control group (3.10 ± 2.54% vs. 1.31 ± 1.15%; 68.67 ± 55.05 ng/mL vs. 27. 36 ± 19.51 ng/mL; respectively, both P < 0.001). Multivariate logistic regression analysis on eosinophil count and serum EDN concentration in predicting recurrent wheezing revealed that the eosinophil count showed the lowest sensitivity (51.6%) and highest specificity (90.4%), with the area under the ROC curve (AUC) of 0.752 ± 0.041; and that, in contrast, the serum EDN showed the highest sensitivity (88.7%) and lowest specificity (56.6%), with AUC of 0.795 ± 0.037. Conclusion Combination of eosinophil count and serum EDN measurement may be better to predict the risk of recurrent wheezing in early life of childhood.